From Social Cohesion to Education: Tahlilan as a Means of Actualising Islamic Education in Society - Jauhari, Roshifah; Falakhina, Arum Nela; Rahmadani, Ahmad Yuhda; Anita, Dewi Evi; Arafah, Siti (Universitas Wahid Hasyim Semarang, 2025)
This study explores the role of the tahlilan tradition in the actualization of Islamic educational values within the community, particularly in Sidomulyo Hamlet, Tanggungharjo Village, Grobogan District, Grobogan Regency. Tahlilan, a long-standing tradition, is often a subject of debate within the community, with some accusing it of being heretical and viewing it as an act of shirk, considering it an evil that must be eradicated. This research aims to delve deeper into how tahlilan functions not only as a religious ritual but also as a means of actualizing Islamic educational values, while simultaneously strengthening social cohesion within society. A qualitative approach with a case study design was employed in this study, involving interviews with religious leaders, observation of tahlilan practices, and documentation of relevant activities. The findings indicate that tahlilan serves as a medium to remind individuals of death and fosters stronger social and spiritual connections among participants. Moreover, tahlilan also acts as a tool for da’wah, enhancing the understanding of Islamic values and encouraging the practice of righteous deeds in everyday life. This research makes a significant contribution to the development of Islamic education, particularly in understanding the role of local traditions as an effective educational tool beyond formal institutions. Keywords: Tahlilan, Values, Islamic Education, Social Cohesion